The perspective of cluster ranking analysis in the development of food safety measures - Anca B\~andoi; Claudiu Bocean; Aurelia Florea; Dalia Simion; Catalina Soriana Sitnikov (Amfiteatru Economic Journal, 2019)
Food safety policies have gained considerable importance in recent years, food safety being one of the indicators that illustrates the standard of living and quality of life within a nation state. In order to assess food security, we analyzed the Global Food Security Index (GFSI) that, economically, is based on GDP, degree of poverty and agricultural production, extending also to areas such as government and public policies, which are usually not directly included in food safety indicators or generating factors. Considering the importance and impact of food safety, starting from the theoretical concepts, from the current state of food safety in Europe, presented by the means of GFSI and its components, we developed a set of measures based on the grouping (correlation) of states following the analysis of hierarchical ranking of clusters. To analyse clusters hierarchical ranking the food safety indicators were used as input, dependent data. As an independent variable, with a strong influence on all the others, determined by means of multiple linear regression, we considered GDP/inhabitant at the level of each analysed state. The design of the set of measures considered the correlation that can be established among the various GFSI indicators that influence and generate the current state of food security in different European countries and the influence these indicators can have on maintaining or improving this state.
Keywords: F52; H55; Q18; C43; 330; Food Safety/Security; Global Food Safety Index (GFSI); hierarchical classification; clusters; GFSI dimensions